Type species designations of Afrotropical Ablaberini and Sericini genera (Coleoptera: Scarabaeidae: Melolonthinae) - Ahrens, Dirk (Zootaxa, 2007)
Type species are designated for 20 genus-group names of Afrotropical Melolonthinae. The following type species designations are made for the tribe Ablaberini: Ablabera Dejean, 1833 (Melolontha splendida Fabricius, 1781); Diplotropis Boheman, 1857 (Diplotropis nigrina Fåhraeus, 1857); Eucamenta Péringuey, 1904 (Camenta transvaalensis Péringuey, 1904); Hybocamenta Brenske, 1898 (Hybocamenta benitoana Brenske, 1898); Paracamenta Péringuey, 1904 (Camenta bohemani Brenske, 1896); and Tulbaghia Péringuey, 1904 (Tulbaghia lightfooti Péringuey, 1904). The following type species designations are made for the tribe Sericini: Allokotarsa Péringuey, 1904 (Allokotarsa clypeata Péringuey, 1904); Alogistotarsa Péringuey, 1904 (Alogistotarsa straminea Péringuey, 1904); Comaserica Brenske, 1897 (Omaloplia conspurcata Blanchard, 1850); Doleroserica Péringuey, 1904 (Doleroserica gentilis Péringuey, 1904); Euronycha Péringuey, 1904 (Euronycha rhodesiana Péringuey, 1904); Hyboserica Péringuey, 1904 (Triodonta caffra Fåhraeus, 1857); Lamproserica Brenske, 1897 (Lamproserica mombasana Brenske, 1901); Loboserica Kolbe, 1914 (Loboserica gracilis Kolbe, 1914); Mesotrochalus Kolbe, 1914 (Mesotrochalus docilis Kolbe, 1914); Onychoserica Moser, 1916 (Onychoserica flabellata Moser, 1916); Phylloserica Brenske, 1899 (Pleophylla brenskei Brancsik, 1892); Pseudotrochalus Quendenfeldt, 1884 (Trochalus sulcipennis Gerstäcker, 1867); Stenoserica Brenske, 1901 (Stenoserica kolbei Brenske, 1901); and Tamnoserica Brenske, 1899 (Omaloplia mutans Blanchard, 1850). The following genus-group name was determined to be unavailable: "Eotrochalus Buregon, 1943" resulting in the following new combinations: Trochalus kisantuensis (Burgeon, 1943), Trochalus motoensis (Burgeon, 1943), and Trochalus puncticeps (Burgeon, 1943). Lectotypes are designated for the following species-group names: Allokotarsa clypeata Péringuey, 1904; Alogistotarsa straminea Péringuey, 1904; Doleroserica gentilis Péringuey, 1904; Euronycha rhodesiana Péringuey, 1904; Lamproserica mombasana Brenske, 1901; Omaloplia conspurcata Blanchard, 1850; Omaloplia mutans Blanchard, 1850; Onychoserica flabellata Moser, 1916; Stenoserica kolbei Brenske, 1901; and Trochalus sulcipennis Gerstäcker, 1867.